2021
DOI: 10.1093/texcom/tgab054
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Spatial Inhibition Processes for Interhemispheric Anti-saccades following Dorsal Posterior Parietal Lesions

Abstract: Anti-saccades are eye movements that require inhibition to stop the automatic saccade to the visual target and to perform instead a saccade in the opposite direction. The inhibitory processes underlying anti-saccades have been primarily associated with frontal cortex areas for their role in executive control. Impaired performance in anti-saccades has also been associated with the parietal cortex, but its role in inhibitory processes remains unclear. Here we tested the assumption that the dorsal parietal cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 118 publications
3
9
0
Order By: Relevance
“…This structure has direct connections with the main cortical ocular motor areas, namely the frontal eye field and the supplementary eye field in the frontal lobe; several (associative, attentional, and motor) areas in the posterior parietal cortex, including the parietal eye field; the cingulate eye field in the anterior cingulate cortex; and the superior colliculus in the brainstem [80]. For the performance of memory-guided saccades, that is, involving short-term spatial memory, visually guided saccades, and antisaccades, the posterior parietal cortex, the dorsolateral prefrontal cortex, and the frontal eye field play significant roles [80][81][82][83]. We found that patients with the post-COVID-19 condition had eye movement alterations mainly in centripetal latency in visually guided saccades, the success rate in memory-guided saccade test, latency in antisaccades, and its standard deviation, which suggests the involvement of frontoparietal networks.…”
Section: Discussionmentioning
confidence: 99%
“…This structure has direct connections with the main cortical ocular motor areas, namely the frontal eye field and the supplementary eye field in the frontal lobe; several (associative, attentional, and motor) areas in the posterior parietal cortex, including the parietal eye field; the cingulate eye field in the anterior cingulate cortex; and the superior colliculus in the brainstem [80]. For the performance of memory-guided saccades, that is, involving short-term spatial memory, visually guided saccades, and antisaccades, the posterior parietal cortex, the dorsolateral prefrontal cortex, and the frontal eye field play significant roles [80][81][82][83]. We found that patients with the post-COVID-19 condition had eye movement alterations mainly in centripetal latency in visually guided saccades, the success rate in memory-guided saccade test, latency in antisaccades, and its standard deviation, which suggests the involvement of frontoparietal networks.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the dorsal PPC results in optic ataxia, consisting of impaired visually guided movements and spatial attention for contralesional visual targets (Pisella et al, 2011, 2021). We have previously shown that unilateral dorsal PPC damage leads to increased ERs for ipsilesional anti‐saccades when the visual target was presented in the contralesional field, particularly for anti‐saccades requiring interhemispheric transfer (Ouerfelli‐Ethier et al, 2021). This specific pattern of lateralized deficits points to the role of dorsal PPC in spatial inhibition of the contralesional visual target.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory processes involved in anti‐saccades are often measured with parameters such as the percentage of erroneous saccades to the visual target or the latency of correctly executed anti‐saccades. These parameters have been measured in different clinical populations, such as Parkinson's disease (Antoniades et al, 2015; Lueck et al, 1990), attention deficit disorder (ADHD) (Fernandez‐Ruiz et al, 2020; Klein et al, 2003), patients with frontal cortex lesions (Fukushima et al, 1994; Guitton et al, 1985) and patients with parietal cortex lesions (Butler et al, 2009; Ouerfelli‐Ethier et al, 2021), and demonstrated impairment of multiple inhibitory processes, including spatial inhibition, response inhibition or proactive inhibition (Aron, 2011; Fernandez‐Ruiz et al, 2020; Hutton & Ettinger, 2006; Munoz & Everling, 2004; Ouerfelli‐Ethier et al, 2021; Talanow et al, 2020; Zhang & Barash, 2000, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most NIBS studies investigating inhibition targeted areas such as the inferior frontal gyrus, DLPFC, and the orbital frontal cortex ( Sarkis et al, 2014 ; Schluter et al, 2018 ; de Boer et al, 2021 ). Inhibition has also been linked to parietal brain regions ( Menon et al, 2001 ; Osada et al, 2019 ; Kolodny et al, 2020 ; Ouerfelli-Ethier et al, 2021 ). This highlights the existence of a frontoparietal network that relates to executive control processes ( Barbey et al, 2012 ; Niendam et al, 2012 ) and inhibition ( Miyake et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%